2016
DOI: 10.7863/ultra.16.02053
|View full text |Cite
|
Sign up to set email alerts
|

Detectability of Hygroscopic Clips Used in Breast Cancer Surgery

Abstract: Sonographically detectable clips were introduced over the last decade. We retrospectively studied the rate and duration of sonographically detectable clip detectability in patients with breast cancer who had sonographically detectable clips inserted over a 2-year period. Nine of 26 patients had neoadjuvant chemotherapy, with all clips remaining detectable 140 to 187 days after insertion. Six of the 9 had intraoperative sonographic localization, with 1 reoperation (17%). Eleven additional patients with nonpalpa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 32 publications
0
18
0
Order By: Relevance
“…The difference between the description from 2005 and the present one may stem from differences in the clips themselves, in the procedure of their placement, or from the fact that in 2005 clips were maintained in the tissue for relatively short periods up to 6 weeks, whereas nowadays the duration is longer and may reach up to 6 months. 9 The pathologic examination of a tissue containing a clip may not be considered complete if the site of the clip is not described. For example, if a hygroscopic clip was placed and viewed by the surgeon in a tumor and the pathologist finds a small malignant tumor in the tissue but can not locate the clip near it, consideration should be taken to verify that the very tumor viewed by the surgeon was indeed found in the tissue grossing.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The difference between the description from 2005 and the present one may stem from differences in the clips themselves, in the procedure of their placement, or from the fact that in 2005 clips were maintained in the tissue for relatively short periods up to 6 weeks, whereas nowadays the duration is longer and may reach up to 6 months. 9 The pathologic examination of a tissue containing a clip may not be considered complete if the site of the clip is not described. For example, if a hygroscopic clip was placed and viewed by the surgeon in a tumor and the pathologist finds a small malignant tumor in the tissue but can not locate the clip near it, consideration should be taken to verify that the very tumor viewed by the surgeon was indeed found in the tissue grossing.…”
Section: Discussionmentioning
confidence: 99%
“…The metal size of this clip is~2 mm. We previously found that it is sonographically visible for at least 6 months after placement, 9 tends not to be displaced with time and enables good cross-modality communication. The degradability of its hygroscopic component may be an additional advantage if the lesion does not have to be removed.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…This might lead to increased patient comfort. In addition, intraoperative monitoring of the removed tissue by ultrasound instead of mammography could probably confirm adequate resection by locating the clip, which would increase the efficiency of the workflow and decrease radiology costs [11]. This could result in a decrease in surgery time, re-excision rates, resection volume, and overall cost [17][18][19].…”
Section: Discussionmentioning
confidence: 99%
“…Since the first description of metal clips in the late 1990s, many different clips have been developed to improve the reproducibility and reliability of breast cancer lesion marking [10,11]. Moreover, as the axillary management of biopsy-confirmed positive lymph nodes might shift from axillary lymph node dissection towards targeted axillary dissection, clip marking of affected lymph nodes might become standard procedure as well [12].…”
Section: Introductionmentioning
confidence: 99%